Laser welding of ultralight magnesium alloy - Tang, Wee Min. (2009)
Magnesium is the lightest metal because of their low density. It alloys have higher strength-to-weight ratios and heat conductivity than other alloys which make it suitable for weight saving constructions in many industries such as automobile, aerospace, telecommunication and microelectronics. Because of the increase applications of magnesium alloys, the joining of magnesium has become an important issue. Laser welding becomes an important technique for joining magnesium alloys as it decrease welding defects and allows for short clock cycles.